THE ROLE OF SELF-EMPLOYED ENTERPRISES IN THE EMPLOYMENT OF THE BLIND - Usmonov Ziyodulla Ulmas o’g’li (Galaxy International Interdisciplinary Research Journal, 2024)
This research aims to critically examine the employment problems of the visually impaired. The dynamics of the number of blind employees of production enterprises under the control of the Society of the Blind of Uzbekistan was analyzed in the period 2014-2023. Factors affecting the problems of these employees were grouped and analyzed. The economic results and social consequences of the reduction in the number of employees in enterprises were studied. Proposals and recommendations were developed to eliminate the above and other problems related to the employment of blind people.